Dual-carbon confined SnO2 as ultralong-life anode for Li-ion batteries. Issue 6 (15th April 2019) - Li, Hui; Zhang, Bao; Zhou, Qijie; Zhang, Jie; Yu, Wanjing; Ding, Zhiying; Tsiamtsouri, Maria A.; Zheng, Junchao; Tong, Hui
Abstract: A composite consisting of SnO2 nanoparticles (approximately 5 nm in size) confined in a dual-carbon framework (SnO2 @C/rGO, where rGO stands for reduced graphene oxide), was prepared using a facile hydrothermal method. The carbon precursors, sodium alginate and graphene oxide (GO), produced a favourable network for the SnO2 nanoparticles, which were encapsulated in amorphous carbon and well-dispersed over the surface of the rGO nanosheets. The SnO2 @C/rGO electrode exhibited notable cycling performance and rate capability as anode material for Li-ion batteries, and maintained a capacity of 844.1 mA h g −1 for over 1000 cycles at the current of density of 1 A g −1 and 525.4 mA h g −1 for over 1700 cycles at 5 A g −1 . Compared with the SnO2 @C and SnO2 /rGO electrodes, the superior electrochemical properties of the SnO2 @C/rGO electrode could be ascribed to the structural stability of the dual-carbon framework as well as the improved electrical conductivity and diffusion coefficient of Li + ions.